Learning curve for laparoendoscopic single-site surgery for an experienced laparoscopic surgeon - Pao-Ling Torng; Kuan-Hung Lin; Jing-Shiang Hwang; Hui-Shan Liu; I-Hui Chen; Chi-Ling Chen; Su-Cheng Huang (Wolters Kluwer Medknow Publications, 2013)
Objectives: To assess the learning curve and safety of laparoendoscopic single-site (LESS) surgery of gynecological surgeries. Materials and methods: Sixty-three women who underwent LESS surgery by a single experienced laparoscopic surgeon from February 2011 to August 2011 were included. Commercialized single-incision laparoscopic surgery homemade ports were used, along with conventional straight instruments. The learning curve has been defined as the additional surgical time with respect to surgical order of LESS surgery, which has been estimated using a smooth function in a linear model with generalized least squares, with some adjustments made due to influencing factors of the operations. Results: All women completed LESS surgeries without the need for ancillary ports, except for two laparotomy conversions due to incidental ovarian malignancy. Three women, one with a gastrointestinal stromal tumor, one with laparoscopic myomectomy, and one who had been receiving simultaneous hysteroscopic myomectomy, were excluded. Of the 58 women included, 39 underwent adnexal surgeries and 19 underwent hysterectomies. Complications occurred with one woman who required a blood transfusion during the procedure. Surgical time was longer in bilateral cystectomy compared with unilateral cystectomy and unilateral/bilateral salpingo-oophorectomy (110.6 ± 51.1 minutes vs. 73.0 ± 26.3 minutes and 66.3 ± 26.9 minutes; p < 0.03); and in laparoscopic total/subtotal hysterectomy (LTH/LSH) compared with laparoscopic-assisted vaginal hysterectomy (LAVH) (205.6 ± 23.3 minutes vs. 120.1 ± 28.6 minutes; P < 0.001). The fitted linear model showed that surgical time was longer in cases with larger adnexal mass, more pelvic adhesion, and more blood loss. Surgical time was longer in LTH/LSH compared with LAVH. Surgical order of LESS surgery was not associated with surgical time. Conclusion: LESS is a safe and feasible alternative to conventional laparoscopic surgery for adnexal and uterine diseases. A learning curve is not required for LESS surgery for experienced laparoscopic surgeons.